Decision Support Systems in Education: A Revolutionary Approach to Teaching and Learning - Perdy Karuru; S Suwarni; Kundharu Saddhono (STAI Hubbulwathan Duri, 2023)
This research investigates how a method known as Simple Additive Weighting (SAW), which is a tool for making decisions based on multiple criteria, might be utilized in the field of education. The goal is to determine the most effective techniques for enhancing the educational process based on a variety of variables, such as student performance, the efficacy of teachers, the relevance of the curriculum, the allocation of resources, and student participation. According to the findings, the solutions that are most likely to be chosen include introducing more interactive teaching methods as well as instituting a school-wide gamification system. However, some limitations of the SAW technique have been recognized. These shortcomings include the method's assumption of the independence of criteria and its sensitivity to weight assignments. The paper's authors concluded by giving suggestions for future research topics. These include the investigation of the impact different weight assignments have on the findings obtained by using the SAW approach, as well as the exploration of other decision-making systems. This research is an important contribution to the expanding body of knowledge on the application of decision-support systems in education and offers insightful information that can be helpful to teachers, school administrators, and policymakers.